LIFESTYLE-RELATED PREDICTORS OF TESTOSTERONE DEFICIENCY AMONG MALE PATIENTS WITH CHRONIC SPINAL CORD INJURY - Sharma, Anil Kumar; Prakash, Om; Urmila, Mahala; Ritika, Parihar (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: In the current study, the author evaluated the prevalence of low testosterone and its independent predictors among male patients with chronic spinal cord injury (SCI). Design: This descriptive type of observational study was conducted in the department of PMR at SMS Medical College. Methods: In this cross-sectional study, 120 patients with chronic SCI were recruited, serum testosterone levels were assessed, and testosterone levels below 300 ng/dL were considered low. The following eight suspected independent predictors for low testosterone levels were assessed: age, body mass index (BMI), nicotine users, total lipid profile, level of injury, American Spinal Injury Association (ASIA) impairment scale, leisure-time physical activity (LTPA) score (h/week) via LTPA questionnaire, and aging male’s symptom (AMS) score via AMS questionnaire. Results: The mean age of the patients was 33.2±7.8 years. Patients with low testosterone exhibited a significant association with dorsal SCI (70.9%), motor complete (ASIA A and B) SCI (76.4%), nicotine use (65.5%), a higher triglyceride (TG) level (168.5 mg/dL), a higher total lipid level (712.9 mg/dL), and a higher AMS score (35.7). Patients with low testosterone were found to be engaged in lower (9.4 h/week) LTPA. A significant negative correlation of total testosterone levels was observed with TG (r=−0.184, p=0.044), total lipid (r=−0.570, p<0.001), BMI (r=−0.504, p<0.001), and AMS scores (r=−0.549, p<0.001). Whereas there was a significant positive correlation observed between total testosterone and LTPA (r=0.380, p<0.001). Conclusion: The prevalence of low testosterone is found at 45.8%, and BMI, LPTA, AMS, and total lipids are identified as independent predictors of low testosterone.